Sustainability and management of the Menzel Habib Aquifer System, Southeastern Tunisia - Dhaoui, Oussama (2020)
In arid and semi-arid areas, the water quantity and quality is a great problem. Salinzation is the major threat in the region of Menzel Habib (north-western Gabès, southeastern Tunisia). The region is a large basin which is essentially represented by sandy-clay formations and bordered by cretaceous reliefs. Geochemical and statistical approaches are reported in the Menzel Habib Aquifer system to examine groundwater salinization processes and factors controlling its mineralization. Geochemical studies were developed in 25 groundwater samples from the shallow aquifer to identify the origin of groundwater salinization. Groundwater geochemistry shows a high correlation between salinity and Na, Cl, Ca, Mg and SO4. These elements are mainly associated to the evaporitic Triassic by dissolution of halite, anhydrite and gypsum which occur on the area and is related to the tectonic context of the region. Additionally, bivariate diagram beween Na and Cl, and Ca and SO4 have also provided a comprehensive understanding of other salinization processes that are involving in Menzel Habib shallow aquifer such as cation exchange and reverse cation exchange.